The Effect of Using Quizlet Application in Improving Students’ Vocabulary Mastery - Rindi Hamida; Atni Prawati; Hadriana Hadriana (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2023)
Technology in education receives a lot of attention because it can help modern learning problems today. The lack of interest and involvement of students during teaching and learning activities motivates teachers to utilize technology for students to increase their interest, especially in vocabulary building in English language learning. To determine whether Quizlet application is effective in expanding students' English vocabulary is the purpose of this research. The design of this research was quasi-experimental with a sample size of 45 seventh-grade students of SMPN 8 Dumai. Students underwent an initial test which was conducted to measure students' initial English word city ability. The post-test was conducted after four treatment meetings, in which the Quizlet application was used as a supporting tool in learning English. In analyzing the collected data, t-test formula and Mann-Whitney test were used. From the analysis, the results showed that the Asym Sig. value was 0.000 < 0.05. This statement shows that the alternative hypothesis (Ha), namely that using the Quizlet application significantly affects the English vocabulary skills of seventh-grade students of SMPN 8 Dumai, is accepted.